Meta Analisis: Pengaruh Tingkat Pendidikan Ibu Terhadap Kejadian Stunting Pada Anak Balita - Alfi Makrifatul Azizah; Ira Nurmala; Shirmarti Rukmini Devy (Universitas Airlangga, 2022)
Background: Stunting is defined as the growth and development of children who fail due to chronic nutritional deficiency, occurs since the child is still in the womb until the age of 2 years, has an impact on the child's growth becoming shorter for his age and experiencing low cognitive impairment. One of the causes of stunting is the low level of education in the mother. Mothers with low education tend to be less knowledgeable about nutritional intake before pregnancy, during pregnancy, and after delivery, so it has an impact on children born with stunting compared to mothers with higher education. Purpose: The study was conducted to analyze the effect of mother's education on the incidence of stunting in children under five. Methods: This study used a meta-analysis study with PICO as follows: P = children under five aged 0-59 months, I = mothers with low education, C = mothers with higher education, O = stunting. Article searches were conducted using electronic databases, namely PubMed and Google Scholar. The search for articles was carried out using the keyword and Mesh method as follows “Maternal Education” AND “stunting” AND “children”. Articles submitted for this meta-analysis study are full-text using a cross-sectional study design. Articles were analyzed using the Review Manager 5.3 application. Results: As many as seven articles from 2017-2021 have been analyzed using PRISMA diagrams. Articles from various journals were found to be from Pakistan, Ethiopia, Rwanda, Burundi, and Nepal. Research studies show that the mother's low education level affects the risk of children under five experiencing stunting by 3.01 times compared to mothers with higher education levels (aOR = 3.01; 95% CI = 1.92 to 4.73), with statistical significance (p = 0.000). Conclusion: The lower the education of the mother, the more influential it is on the occurrence of stunting in children under five.